Antibacterial and Antioxidant Activities of Triterpenoids Isolated from Endemic Euphorbia arbuscula Stem Latex - Zainab Al-Ansi; Mohammed Masaoud; Khaled Hussein; Bushra Moharram; Wafa M. Al-Madhagi (Advances in Pharmacological and Pharmaceutical Sciences)
This research study aimed to investigate the chemical constituents and evaluate the antibacterial and antioxidant activities of stem latex extracts from the endemic medicinal plant Euphorbia arbuscula found on Socotra Island, Yemen. The study aimed to assess the potential medicinal and veterinary uses of this plant, representing the first evaluation of its properties. The stem latex was extracted using ethanol, and the resulting oil underwent analysis using GC-MS to identify eight compounds. In addition, chromatographic techniques were employed to isolate two triterpenoids, lanosterol and lupeol, from the stem latex. The structures of these compounds were confirmed using IR, MS, and NMR techniques. The antibacterial activity of the extracts and isolated compounds was evaluated against three bacterial strains using the disc diffusion method, revealing only weak antibacterial effects. The study also investigated the antioxidant activity using the DPPH assay, where the ethyl acetate extract exhibited the highest activity with an IC50 value of ±13.55 µg/mL, followed by the chloroform extract with an IC50 of ±21.87 µg/mL. These findings emphasize the potential of Euphorbia arbuscula in the development of new medicines, particularly due to its notable antioxidant activity. The research methodology employed a scientifically rigorous approach, utilizing a comprehensive range of analytical techniques. However, further investigation is required to fully assess the plant’s potential as a therapeutic agent.